Edukasi Penanganan Sindrom Premenstruasi (PMS) dengan Latihan Yoga - Juhrotun Nisa; Adevia Maulidya Chikmah; Puji Tri Astuti; Novia Ludha Arisanti; Siti Khumayah; Siti Habibah (Jurnal Surya Masyarakat, 2025)
PMS conditions that are not treated properly in some women can disrupt their quality of life. One of the therapies recommended by the international organization The Royal College of Obstetricians and Gynecologists in managing PMS symptoms is exercise. Yoga is a form of exercise that can be done before menstruation. With Yoga, the mind calms and relaxes the body so that it can control stress, anxiety, depression and also overcome dysmenorrhea. This service activity was carried out with the aim of providing education on premenstrual syndrome  treatment with yoga exercises. The activity method is carried out by providing Health Education using slides and leaflets, as well as practicing yoga poses with a certified instructor. Measurement of educational success is carried out through pretest and posttest. Community service activity in partnership with the family learning center (PUSPAGA) on January 5 2024 at Politeknik Harapan Bersama, Tegal City, with 36 young women participating from 6 high schools in Tegal City. The results of the activity showed that there was an increase in knowledge after providing health education about treating PMS with yoga practice. The importance of the role of relevant agencies in providing health information and monitoring physical activity of adolescents at school age.